Pengaruh Stres Kerja Dan Konflik Kerja Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang (DPUPR) Kabupaten Karawang - Fikiana Fikiana; Budi Rismayadi; Wike Pertiwi (UNIVED Press, 2023)
This study aims to determine the effect of work stress and work conflict on employee performance at the public works and spatial planning office (DPUPR) of Karawang Regency. This study uses a verification method with saturated sampling data collection techniques. In this study, a sample of 100 employee respondents was used at the public works and spatial planning office (DPUPR) of Karawang Regency. The results of the study were analyzed using the SPSS application with multiple linear regression analysis. The results indicate that (X1) work stress has a significant and negative effect on employee performance, but (X2) work conflict has a positive and significant effect on (Y) employee performance. From the results of the simultaneous test analysis as much as 83.7%. assessment of work stress and work conflict affects employee performance at the public works and spatial planning office (DPUPR) of Karawang Regency